Strategi Komunikasi Lingkungan Ekowisata Taman Mangrove Jung Koneng Bangkalan untuk Rehabilitasi - Pratama, Rafly Putra (Calathu: Jurnal Ilmu Komunikasi, 2024)
Examining the environmental communication strategy implemented by the Payung Kuning Tourism Awareness Group as the manager of the Jung Koneng Mangrove Park in Labuhan Village, Ten District, Bangkalan. Starting from damage to the coastal environment due to the behavior of people who do not care about the sustainability of the mangrove ecosystem, as well as uncontrolled piles of rubbish, resulting in a significant decline in environmental quality. Using descriptive qualitative methods, researchers identified strategic steps in environmental communication which were grouped into four main stages, namely situation analysis, planning, media production, and action and reflection. At the situation analysis stage, Pokdarwis identified the environmental problems faced and the actors involved in mangrove rehabilitation. The planning stage involves developing a communication strategy based on local conditions, collaboration with external parties, and the use of traditional and digital media. In the media production stage, various communication channels such as social media, face-to-face discussions, and visual learning media are used to convey educational messages. The final stage, action and reflection, focuses on implementing rehabilitation activities and evaluating the impact of the communication strategies that have been implemented. Community participation not only contributes to the successful rehabilitation of the mangrove ecosystem, but also increases the community’s social and economic awareness regarding ecotourism potential. Keywords: environmental communication strategy, mangrove, ecotourism, education, Jung Koneng Mangrove Park